1990
DOI: 10.1021/np50068a021
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Agents, 112. Emarginatine B, a Novel Potent Cytotoxic Sesquiterpene Pyridine Alkaloid from Maytenus emarginata

Abstract: A new sesquiterpene pyridine alkaloid, emarginatine B [2] has been isolated, along with maytansine [3], from Maytenus emarginata. Emarginatine B showed potent cytotoxicity against human KB cells (ED50 = 0.4 micrograms/ml). Spectral correlations established its structure as a 9-benzoate and C-8 epimer of emarginatine A [1]. The conformational aspect of the latter compound was elucidated by nmr studies, including the use of 2D-nmr techniques and difference nOe methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…The authors also have identified cytotoxic sesquiterpene pyridine alkaloids, including emarginatines B (I7) and F (I8), from M. emarginata (Willd.) Ding Hou (90,91). Recently, new triterpenes were isolated from M. chuchuhuasca R. Hamet and Colas (92), along with sesquiterpenes from the same plant (93).…”
Section: Maytenus Speciesmentioning
confidence: 99%
“…The authors also have identified cytotoxic sesquiterpene pyridine alkaloids, including emarginatines B (I7) and F (I8), from M. emarginata (Willd.) Ding Hou (90,91). Recently, new triterpenes were isolated from M. chuchuhuasca R. Hamet and Colas (92), along with sesquiterpenes from the same plant (93).…”
Section: Maytenus Speciesmentioning
confidence: 99%
“…M. diversifolia contains the related maytanprine (M6), which shows growth-inhibiting and apoptosis-inducing activities in [132]. The authors also identified cytotoxic sesquiterpene pyridine alkaloids, including emargintines B (M7) and F (M8), from M. emarginata [133,134]. Recently, M. chuchuhuasca yielded new triterpenes [135] and sesquiterpenes [136], and antitumor promoting sesquiterpenes were also isolated from M. cuzooina [137].…”
Section: Anticancer and Antitumor Compoundsmentioning
confidence: 99%
“…Sesquiterpene pyridine alkaloids are a large group of highly oxygenated sesquiterpenoids, and are predominantly isolated from the plants of the family Celastraceae [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These alkaloids have significant biological activities, such as their immunosuppressive [5,15], insect antifeedant, insecticidal [9,16], anti-HIV [6,11,12], antitumor [1,2,17] and antiplasmodial activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…These alkaloids have significant biological activities, such as their immunosuppressive [5,15], insect antifeedant, insecticidal [9,16], anti-HIV [6,11,12], antitumor [1,2,17] and antiplasmodial activities [13]. Rapid and sensitive analysis for these compounds remain desirable.…”
Section: Introductionmentioning
confidence: 99%